Application of prospect theory to microinsurance based on contingent valuation approach for poor population in Ukraine - Shirinyan, Aram; Shirinyan, Lada (My University, 2023)
This paper takes a behavioral economics approach and empirically tests if Prospect Theory can explain behavior of low-income people in Ukraine. The study uses the contingent valuation method due to direct inquiry of low-income people, in a survey, how much they would be willing to pay for insurance and to get back in case of an insurance event arising. This paper provides suggestive evidence that according to Prospect Theory poor individuals make decisions based on expectations of loss or gain from their current relative position and are more sensitive to losses compared to gains. The work also answers the question concerning the microinsurance: can microinsurance be a business proposition and provide value for low-income people at the same time? The results lead to the power-law distribution of potential clients according to the price of a microinsurance service. The obtained correlations help to formulate strategies to tap the low-income market in the country. Ця стаття використовує підхід поведінкової економіки та емпірично перевіряє, чи може теорія перспектив пояснити поведінку людей з низькими доходами в Україні. У дослідженні використовується метод контингентної оцінки за рахунок прямого опитування малозабезпечених людей, в ході опитування, скільки вони готові були б заплатити за страховку та отримати назад у разі настання страхового випадку. У цьому документі наводяться переконливі докази того, що згідно з теорією перспектив бідні люди приймають рішення, ґрунтуючись на очікуванні втрат або вигод від свого поточного відносного становища, і більш чутливі до втрат, ніж до вигод. Робота також відповідає на запитання щодо мікрострахування: чи може мікрострахування бути бізнес-пропозицією і водночас приносити користь людям з низькими доходами? Отримані результати призвели до степеневого розподілу потенційних клієнтів за ціною послуги мікрострахування. Отримані кореляції допомагають сформулювати стратегії виходу на ринок з низькими доходами в країні.
Keywords: кафедра фінансів; microinsurance; prospect theory; contingent valuation; low-income people; subjective utility; мікрострахування; теорія перспектив; умовна оцінка; малозабезпечені люди; суб'єктивна корисність